Does the Increase in Competition between Schools Improve the Quality of the Service? The Role of Educational Reform in Chile. Issue 8 (3rd August 2019) - Cartagena FarÍas, Javiera; McIntosh, Steven
Abstract: We analyse the effect of geographic competition between schools on academic performance in Chile. The analysis controls for prior pupil performance, and a range of school and municipality characteristics. We allow for the endogeneity of voucher school location, using the number of local Catholic churches as an instrument. We find that a larger number of public schools positively affects the quality of education of other schools located in the same area, particularly amongst middle-class families and in middle-ranking schools. However, the number of voucher schools is associated with lower performance in neighbouring schools, which we attribute to pupil sorting.